PEMANFAATAN LIMBAH KULIT BUAH PISANG KEPOK (Musa paradisiaca) SEBAGAI BIOSORBEN ZAT WARNA RHODAMIN B - Musafira Musafira; Nurfitrah M Adam; Dwi Juli Puspitasari (KOVALEN: Jurnal Riset Kimia, 2019)
The investigation about the utilization of Banana peel (Musa paradisiaca) as biosorbent Rhodamine B dye has been done The purpose of this study was to determine the maximum contact time and to determine the adsorption capacity of kepok banana peel. Completely randomized design (CRD) was used in this research with two variables (the contact time and Rhodamine B concentration. Both variables were done in five levels i.e 10, 30, 60, 90, and 120 min and 2, 4, 6, 8 and 10 ppm respectively. The result showed that the maximum concentration of banana peel in adsorbing Rhodamine B was 6 ppm with 120 of contact time, and Rhodamine B adsorption capacity was 4.55mg/g. Keywords: Banana peel, Rhodamine B, biosorbent